Is Prematurity a Protective Factor Against Developmental Dysplasia of the Hip? A Retrospective Analysis of 660 Newborns - Koob, Sebastian; Garbe, Werner; Bornemann, Rahel; Ploeger, Milena Maria; Scheidt, Sebastian; Gathen, Martin; Placzek, Richard (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose In Middle Europe developmental dysplasia of the hip (DDH) has an incidence of up to 5.9 %. The rate of congenital hip dislocation as the worst complication of a growth disorder of the hip is between 1.5 % and 2.5 %. Among known risk factors of DDH are breech position, multiples, foot deformities and family history. The aim of this retrospective study was to investigate prematurity as a risk factor for developmental dysplasia of the hip (DDH).Materials and Methods The hips of 283 infants who were born before the 38th week of gestation or earlier, and those of 377 infants who were born after the 37th week of gestation, none of whom had other risk factors for DDH, were compared using the ultrasound technique according to Graf et al., within the first week after birth. Both hips of all infants were included in the study.Results Surprisingly, the difference in alpha angles between the two groups was statistically extremely significant, favoring the preterm infants. Moreover, we found a physiological curve of alpha angle development with a peak after the 31st week of gestation. The incidence of pathological dysplasia was not significantly different in the two groups.Conclusion Our results suggest that prematurity is not a predisposing factor for DDH, but rather is protective for hip development.
Keywords: graf ultrasound; hip development; congenital hip dysplasia; hip ultrasound screening; developmental dysplasia of the hip